2013
DOI: 10.1371/journal.pone.0064299
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pfmdr1 and Pfcrt in Changing Chloroquine, Amodiaquine, Mefloquine and Lumefantrine Susceptibility in Western-Kenya P. falciparum Samples during 2008–2011

Abstract: Single Nucleotide Polymorphisms (SNPs) in the Pfmdr1, and Pfcrt, genes of Plasmodium falciparum may confer resistance to a number of anti-malaria drugs. Pfmdr1 86Y and haplotypes at Pfcrt 72-76 have been linked to chloroquine (CQ) as well as amodiaquine (AQ) resistance. mefloquine (MQ) and lumefantrine (LU) sensitivities are linked to Pfmdr1 86Y. Additionally, Pfcrt K76 allele carrying parasites have shown tolerance to LU. We investigated the association between Pfmdr1 86/Pfcrt 72-76 and P. falciparum resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 44 publications
(61 reference statements)
10
96
1
Order By: Relevance
“…In Kenya, this decline was first reported in Kilifi in 2006, 13 years after the discontinuation of CQ use (28), in which the prevalence of the Pfcrt K76T mutation was shown to decrease from ϳ95% in 1993 to ϳ60% in 2006. Studies from western Kenya demonstrated that in 2008, the prevalence of parasites with the Pfcrt CVIET genotype was 72.4%, which was shown to decline to 32.1% by 2011 (44). During our study period, we observed a reduction of the prevalence of this genotype to 7% by 2013, demonstrating that the prevalence of this genotype is on the decline.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In Kenya, this decline was first reported in Kilifi in 2006, 13 years after the discontinuation of CQ use (28), in which the prevalence of the Pfcrt K76T mutation was shown to decrease from ϳ95% in 1993 to ϳ60% in 2006. Studies from western Kenya demonstrated that in 2008, the prevalence of parasites with the Pfcrt CVIET genotype was 72.4%, which was shown to decline to 32.1% by 2011 (44). During our study period, we observed a reduction of the prevalence of this genotype to 7% by 2013, demonstrating that the prevalence of this genotype is on the decline.…”
Section: Discussionsupporting
confidence: 49%
“…In 2007, the prevalence of parasites with the Pfmdr-1 N86Y mutation in western Kenya was shown to be ϳ69% (45). However, a steady decline in the prevalence of this mutation was subsequently observed, from 42% in 2008 to 30% in 2009, 28% in 2010, and 15% in 2011 (44). Our study showed a decline in prevalence from 18% in 2010 to 0% by 2013.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Most of P. falciparum isolates collected from Thailand carry pfcrt mutations at codons K76T, A220S, Q271E, N326S and R371I [7] . The mutation at codon 86 of pfmdr1 (86Y) related with chlolroquine resistance, while pfmdr1 wild type at the same codon (N86) including increased pfmdr1 gene copy number linked to resistance of the parasite to mefloquine and artesunate [8][9][10] . The aim of the present study was to investigate the distribution and patterns of pfcrt and pfmdr1 polymorphisms in P. falciparum isolates collected from the malaria endemic area of Thailand along Thai-Myanmar border.…”
Section: Introductionmentioning
confidence: 99%
“…N86 allele in Pfmdr1 has been shown in vitro in conferring less susceptibility to artesunate. 49 Few isolates from Arunachal Pradesh have been 51 Exact association of Pfmdr1 and PfK13 mutations in resistance development cannot be ascertained as study reports including these 2 genes are not sufficiently available. Wild-type N86 allele in Pfmdr1 has been found with increased tolerance to both artemether and lumefantrine separately.…”
Section: Discussionmentioning
confidence: 99%